SCOUTING IN CONTEMPORARY BASKETBALL - Csilla GRĂDINARU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2017)
Scouting in basketball means spying and carefully exploring to get information on basketball players. Finding valuable basketball players and integrating them in a team ensures a high quality, spectacular game that attracts the public. In this paper, the author defines the most important factors that contribute to the analysis and choice of players for a competing team. We emphasise the goals and ways of making scouting effective. Our goal was to see if a scouter's activity is useful in athletic performance. To do so, we used literature, observation, video recordings, questionnaires, and interviews. We designed a questionnaire with seven items related to scouting in contemporary basketball. We asked six scouters to answer the following open questions related to their activity of "talent seekers": When do you scout for basketball players? (When do you monitor basketball players?) What are your criteria in choosing basketball players? What do you seek for in a basketball player? How do you contact basketball players? How do you know they meet your basketball club's demands? How do you sign a contract with a basketball player? (What are the steps you follow?) Do you benefit of a percentage of the contracts or does the basketball club pay you? (This question is not mandatory). The most important criterion in choosing a basketball player is his ability of integrating into the game model and team structure (66% of the respondents). The scouters interviewed believe that a player's individual value comes first in choosing him for the club. A period of testing and the choice of information from the player's previous colleagues or coaches determine a player's choice. Scouting is a particularly important activity when performance is aimed at. Effective scouting helps discover the suitable basketball player, which can make a difference between failure and success.